50 Years in Neurology, A Retrospect. Issue 1 (1st February 2003) - Unknown
Abstract : I had not come across Practical Neurology until I received a recent issue from the Editor. Having now seen it, I am impressed by its content and format and was particularly interested to read two of the articles. The first on myositis reminded me of my second monograph, published with Raymond Adams in 1956, which was on the topic of polymyositis. I also enjoyed the article by Julian Fearnly on superficial siderosis of the nervous system, because Bernard Tomlinson and I published a comprehensive review of the topic and reported a case resulting from an ependymoma of the lateral ventricle back in 1964. Reading these articles and others giving practical advice to practising neurologists led me to reflect, now that I am 80 years of age, on my early years in neurology and on some lessons I have learned during a lengthy career in teaching, research and clinical practice. When